CRISPR-Cas9 and Its Bioinformatics Tools: A Systematic Review - Alicja Jasieniecka; Inês Domingues (Current Issues in Molecular Biology)
CRISPR-Cas9 has revolutionized genetic research with bioinformatics tools essential for tasks like guide RNA design, off-target prediction, and data analysis. This systematic review summarizes the functionality and key features of such tools. Studies published after 2012 were selected through searches in PubMed, Google Scholar, and other sources, with the final search conducted on 9 November 2024. Seven studies met the criteria, describing around 45 tools, including databases and functional programs. Tools like CRISPResso, CHOPCHOP, and Cas-OFFinder were commonly highlighted, with a major focus on single-guide RNA (sgRNA) design and optimization. Some tools provided specific solutions, while others offered broader functionality, but most lacked experimental validation. Several tools were developed by the authors of the studies, introducing potential bias. Findings highlight a need for integrated platforms that combine functionalities, reducing reliance on fragmented workflows. Current tools often address narrow tasks, complicating their practical application. Future development should focus on comprehensive, multitasking tools to improve accessibility and streamline research processes. Limitations include the descriptive nature of most studies, potential author bias, and challenges in comparing tools objectively. Nonetheless, this review underscores bioinformatics’ critical role in CRISPR research and emphasizes the need for innovative, standardized platforms. This study received no funding and was not registered.